Country Partnership Framework for Solomon Islands for the Period FY2018-FY2023 - World Bank Group (World Bank, Washington, DC, 2018)
This country partnership framework (CPF) for Solomon Islands spans the period from July 1, 2017, to June 30, 2023 (FY2018-FY2023). It presents the World Bank Group’s (WBG) program of engagements over this period and a results framework against which anticipated outcomes will be evaluated. It builds on the results and lessons of Solomon Islands’ previous country partnership strategy (CPS), which covered the period between FY2013 and FY2017. This CPF is well aligned with the Solomon Islands Government’s (SIG’s) long-term development vision, the national development strategy 2016 to 2035: improving the social and economic livelihoods of all Solomon Islanders (NDS), and the thematic priorities emerging from the WBG’s Solomon Islands systematic country diagnostic (SCD), completed in June 2017. The main purpose of the CPF is to support Solomon Islands in enhancing its economic resilience through inclusive growth, while considering economic geography and state fragility. The CPF will selectively support Solomon Islands’ medium-term development plan (MTDP): 2016 to 2020 and incorporates key priorities of the SCD. The CPF is organized around three focus areas: (i) strengthening the foundations of well-being, (ii) promoting inclusive and sustainable growth, and (iii) managing uneven development.